Handbook of research on business transformations in the era of digitalization - Mezghani, Karim, 1979-; Aloulou, Wassim, 1972- (Business Science Reference, 2019)
"This book identifies the latest trends, business opportunities and challenges linked to digitalization, defines concepts in relation with business transformations caused by digitalization, and shares useful experiences and best practices to deal with the new technological changes"--